If it's not what You are looking for type in the equation solver your own equation and let us solve it.
39(x+2)+x=4(x-1)+10
We move all terms to the left:
39(x+2)+x-(4(x-1)+10)=0
We add all the numbers together, and all the variables
x+39(x+2)-(4(x-1)+10)=0
We multiply parentheses
x+39x-(4(x-1)+10)+78=0
We calculate terms in parentheses: -(4(x-1)+10), so:We add all the numbers together, and all the variables
4(x-1)+10
We multiply parentheses
4x-4+10
We add all the numbers together, and all the variables
4x+6
Back to the equation:
-(4x+6)
40x-(4x+6)+78=0
We get rid of parentheses
40x-4x-6+78=0
We add all the numbers together, and all the variables
36x+72=0
We move all terms containing x to the left, all other terms to the right
36x=-72
x=-72/36
x=-2
| 5y-6=2y-42 | | 3(x-2)=3x-4 | | 5x+52=3x-16 | | 12,4=6a-2 | | 6x-(2x-9)=-31 | | 61y-15=-137 | | 122=2w+35 | | 8w-18=14 | | 16x-3=269 | | 10x+1=12x+7 | | 10x+-1=12x+7 | | 8+2(x-6)0=-2+2x-2 | | 3v+15=33 | | -24=2(x+5) | | x(3x-12)=96 | | 13x+5=8x-+14 | | x+8=2x+10 | | -4w-5=-41 | | -7(-4-6j)=2+194 | | F(x)=3/x+2 | | 10=p/2-2 | | -3c=-18.9 | | 2(2x-1)=(x+1 | | 369-18=-9(-3-4v) | | t−14=-12.5 | | 28=-7(2z+4) | | 14z=616 | | 16p=432 | | x-8+3x=4(x-2) | | n17=16 | | 5(5x+3)+5x=20x+55 | | 13z=520 |